Preliminary ecology research on Epipactis atrorubens (Hoffm.) Besser on the Słowińskie Coast (Northern Poland) - Parzych, Agnieszka; Sobisz, Zbigniew (Ecological Questions, 2014)
The research covered three stands of Epipactis atrorubens on the Słowińskie Coast (Rowy, Wicko Morskie and Jarosławiec). The plants in blossom were characterized on the basis of seven individual characteristics: height, the number of leaves, the number of flowers per inflorescence, the length and width of the largest leaf and stipule. Statistically significant differences were found in the studied populations between the height of the plant and the width of the largest leaf, the number of flowers per inflorescence and the inflorescence length up to the bract, as well as between the number of flowers per inflorescence and the inflorescence length up to the bract. The populations of E. atrorubens on the Słowińskie Coast cover the mineral soil with the dominance of medium- and fine sand fractions. Those soils are loose with very low water capacity and good permeability. The organic matter content varied from 0.4 to 0.8%. The soil reaction is low acid or close to alkaline. The analyzed soil samples were characterized by very low content of exchangeable Al3+ ions, which results from relatively high pH levels. The soil salinity was low and the average content of NaCl was between 0.146 and 0.181 g·dm-3.